An ethical pathway for the use of Artificial Intelligence in Medicine and Nursing Care - Paladino, María Soledad (Medicina e Morale, 2023)
Modern Medicine faces the challenge of acquiring, analyzing, and applying a great amount of data to solve a complex quantity of clinical problems. In this scenario, Artificial Intelligence technologies serve the developing of programs to help professionals diagnose, predict results, and make therapeutic decisions. The same as any technology applied to man, the use of Artificial Intelligence poses ethical questions. In this article the principal ethical problems related to the use of Artificial Intelligence technologies in Medicine are identified and a roadmap for reflection on the former from the praxis perspective is suggested. Nursing is no stranger to the revolutionary change brought about by the introduction of Artificial Intelligence in health care. The recent conclusions of the international think-tank on Artificial Intelligence and Nursing recognized the relevance of the use of these technologies to increase and extend the capabilities of Nursing, including care. Nursing practice raises the question about the impact of Artificial Intelligence technologies on the very essence of Nursing, that is, on the nurse-patient relationship by providing good care. From Nursing epistemology, it is to possible sketch out a pathway for reflection on the ethical problems raised by the use of Artificial Intelligence technologies.